The Effect of Burnout and Job Satisfaction on Turnover Intention at PT Jonan Indonesia - Arumsari Arumsari; Enjang Suherman; Laras Ratu Khalida (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of burnout and job satisfaction on turnover intention in PT Jonan Indonesia. To prevent the turnover rate from increasing, the company must be able to observe the factors that drive employees to decide to leave the company. The driving factors for turnover intention can consist of various things, including burnout and job satisfaction. The research method used is a quantitative descriptive approach. The data analysis technique uses likert measurement and multiple linear analysis with the help of SPSS version 26. The population of this study was 172 employees of PT Jonan Indonesia and the sample determination used random sampling with 5% slovin which resulted in 120 samples. The results showed that burnout had a positive and significant effect on turnover intention, and the effect of job satisfaction on turnover intention had a negative and significant effect. The simultaneous influence shows that burnout and job satisfaction together have a significant influence on turnover intention. From the results of the calculation of the Coefficient of Determination (R Square) of 0.773, it indicates that 77.3% of the variation in turnover intention can be explained by burnout and job satisfaction. The rest, at 22.7%, was influenced by other factors outside the research model.